LINE-1 retrotransposon activation drives age-associated inflammation via cytoplasmic cDNA-STING/type I interferon signalling: therapeutic potential of reverse transcriptase inhibition - Mehmood, Arshad; Xue, Yue Zhu; Yassin, Habab Merghani; Zubair, Mohammad; Rahmat, Syed Adnan; Ahmad, Aftab (Contemporary Oncology/Współczesna Onkologia, 2025)
Retrotransposable elements are harmful at several levels, and host surveillance systems fail to consider all these elements in severe effects. The key role of retrotransposon in aging and age-associated diseases remains unclear. We summarise whether LINE-1 retrotransposable elements transcriptionally derepress and activate type-I interferon response during cellular senescence. Type-I interferon response is the late senescence phenotype that maintains the senescence-associated secretory phenotype. Cytoplasmic LINE-1 cDNA activates type-I interferon response, while LINE-1 reverse transcriptase inhibitors suppress it. The nucleoside reverse transcriptase inhibitor lamivudine downregulates activation of type-I interferon and age-associated inflammation in tissues in the treatment of aging. Activation of retrotransposons is a key factor in sterile inflammation, which is a hallmark of aging, and LINE-1 reverse transcriptase is an important target for the treatment of age-associated diseases. Nucleoside reverse transcriptase inhibitor lamivudine downregulates activation of type-I interferon and age-associated inflammation.